2019
DOI: 10.1103/physrevb.100.125422
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit coupling in elemental two-dimensional materials

Abstract: The fundamental spin-orbit coupling and spin mixing in graphene and rippled honeycomb lattice materials silicene, germanene, stanene, blue phosphorene, arsenene, antimonene, and bismuthene is investigated from first principles. The intrinsic spin-orbit coupling in graphene is revisited using multi-band k · p theory, showing the presence of non-zero spin mixing in graphene despite the mirror symmetry. However, the spin mixing itself does not lead to the the Elliott-Yafet spin relaxation mechanism, unless the mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 53 publications
4
39
0
Order By: Relevance
“…However, the spin-orbit coupling can lead to a reduction of m z , while preserving m x = m y = 0, as shown in Ref. [30] for 2D hexagonal crystals. Nevertheless, in most cases, taking m z = 1/2 was demonstrated to be a reasonable approximation [31].…”
Section: Introductionmentioning
confidence: 77%
“…However, the spin-orbit coupling can lead to a reduction of m z , while preserving m x = m y = 0, as shown in Ref. [30] for 2D hexagonal crystals. Nevertheless, in most cases, taking m z = 1/2 was demonstrated to be a reasonable approximation [31].…”
Section: Introductionmentioning
confidence: 77%
“…1a reveal that all the conduction and valence bands around the K -points are spin split because of spin–orbit coupling. The combination of mirror-plane and time-reversal symmetry suggests that spin in the out-of-plane direction, S z , is a good quantum number with opposite orientations in the + K and − K -valleys 28 , 29 . Figure 2e shows the CB+2 − band, color-coded by the calculated 〈 S z 〉 expectation value.…”
Section: Resultsmentioning
confidence: 99%
“…1 . Similar to other buckled 2D materials made of group V elements, such as blue phosphorene, arsenene or antimonene 22 , the band gap of monolayer nitrogene is indirect. The size of the indirect gap for the PBE exchange correlation functional is , eV, and is in agreement with the values reported by others 13 .…”
Section: Resultsmentioning
confidence: 81%
“…Nitrogen is a light element with the atomic number Z=14. Therefore, spin–orbit coupling (SOC) in nitrogene is expected to be weak 22 , similar to graphene 23 and phosphorene 12 . Indeed, in a recent theoretical study, Lee et al 10 observed no significant effects of SOC on the band structure of buckled nitrognene.…”
Section: Introductionmentioning
confidence: 99%